Association between hydrochlorothiazide exposure and different incident skin, lip and oral cavity cancers: A series of population‐based nested case–control studies. Issue 7 (2nd March 2020) - Morales, Daniel R.; Pacurariu, Alexandra; Slattery, Jim; Kurz, Xavier
Abstract : Aims: Hydrochlorothiazide‐induced photosensitivity may increase squamous cell carcinoma (SCC), basal cell carcinoma (BCC) and lip cancer risk. The aim was to quantify these risks. Methods: Nested case–control studies using data from the UK THIN database from 01 January 1999 to 01 May 2016. Adults with incident SCC, BCC, melanoma, lip cancer and oral cancer were matched (on age, sex and calendar year of cohort entry) to controls using incidence density sampling. Incidence rate ratios (IRR) for each outcome were calculated for ever and cumulative hydrochlorothiazide exposure, measuring the impact of additionally adjusting for smoking and body mass index (BMI). Adjusted rate differences were estimated, including the number needed to harm. Results: Cumulative hydrochlorothiazide doses ≥50 000 mg were associated with a significantly increased risk of SCC IRR = 3.05 (1.93–4.81) and BCC IRR = 1.34 (1.06–1.69). Using a 5‐year lag‐period, hydrochlorothiazide exposure was also associated with a significantly increased risk of lip cancer (IRR 2.85, 95% confidence interval 1.32–6.15). No significantly increased risk of melanoma or oral cavity cancer was observed. Following adjustment for smoking and BMI, which had inverse associations with several skin cancer types, associations for hydrochlorothiazide remained significant. The overall number needed to harm with high‐dose cumulative hydrochlorothiazide exposure was: 804 for SCC; 2463 for BCC, and 200 000 for lip cancer but varied by age and sex. Conclusion: Hydrochlorothiazide exposure was associated with an increased risk of SCC, BCC and lip cancer that is not explained following adjustment for smoking and BMI. These findings may support clinical and regulatory decision making.